Effectiveness of mobile technology and utilization of maternal and neonatal healthcare in low and middle-income countries (LMICs): a systematic review - Prasenjit De; Manas Ranjan Pradhan (BMC, 2023)
Abstract Background Maternal and neonatal mortality are important indicators of the development of a nation and pose a severe health concern, especially in developing and Low and Middle-Income Countries (LMICs). Healthcare providers use various mobile technologies as tools to provide antenatal, delivery, and postnatal care and thereby promote maternal and child health. We conducted a systematic review to critically assess the existing literature on the effectiveness of mobile phone technology in maternal and neonatal healthcare (MNH) utilization, especially in LMICs in Asia and Africa. Methods A systematic search strategy was developed, and Boolean combinations of relevant keywords were utilized to search relevant literature on three electronic databases (PubMed/Medline, Scopus, and Google Scholar) from 2012 to 2022. After assessing the inclusion and exclusion criteria, 25 articles were selected for systematic review. A narrative synthesis strategy was applied to summarise the information from the included literature. Results This review reveals that research and evaluation studies on mobile phone or Mobile Health (mHealth) and MNH service utilization substantially varied by research designs and methodology. Most studies found that mobile phone technology is highly appreciable in improving several MNH indicators, especially in LMICs. Despite the identified benefits of mobile technology in MNH utilization, some studies also mentioned challenges related to technology use and misuse, rich-poor discrimination, and disparity in phone ownership need to be addressed. Conclusion There is constantly increasing evidence of mobile counseling and the use of digital technology in the MNH care system. Public health practitioners and policymakers need to make efforts to smooth the functioning of technology-based healthcare services, considering all the issues related to the confidentiality and safety of health-related data on the Internet.